Persepsi Pemutihan sebagai Variabel Moderasi terhadap Pengaruh Sistem, Pelayanan, Kesadaran Wajib Pajak dan Sanksi Pajak pada Kepatuhan Pajak Kendaraan Bermotor di SAMSAT Jombang - Fauzi Ardiansyah; Sjarief Hidajat (IPM2KPE, 2024)
This research aims to analyze and explain the influence of systems, services, taxpayer awareness and tax sanctions on motor vehicle taxpayer compliance in the Jombang One-Stop Manunggal Administration System (SAMSAT) with perceptions of whitening as a moderating variable. This research uses a quantitative research approach. The population in this study were all motor vehicle tax payers registered with SAMSAT Jombang. Sampling technique using the Slovin formula. The total taxpayer population is 637,796 taxpayers who own motor vehicles. The sample obtained consisted of 100 taxpayers. With data collection techniques using questionnaires. The analytical method used in this research is Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. Testing the questionnaire results uses validity analysis and reliability analysis. The research results show that it can be concluded that the results of research on systems, services, awareness, sanctions have no positive and insignificant effect on taxpayer compliance. Perception of bleaching as a moderating variable has no positive and insignificant effect on systems, services, awareness, sanctions, and taxpayer compliance. Taxpayers do not comply with paying taxes on time in the hope of not receiving high sanctions if they are late or do not pay taxes with the existence of tax whitening moderation. Keywords: Awareness, Service, Tax Collection, System, Sanctions